Seasonal Occurrence of the Indian Ocean Blue Whale (Balaenoptera musculus indica) off South Coast of Sri Lanka - Upul S. P. K. Liyanage; Pradeep K. P. B. Terney; Upali S. Amarasinghe; Kanapathipillai Arulananthan; Marianne Helene Rasmussen (Journal of Marine Science and Engineering, 2023)
This paper describes the distribution, abundance and seasonal variation in blue whales (BWs) on the south coast of Sri Lanka, off Mirissa, where they are faced with anthropogenic threats. Data collection encompassed opportunistic sightings by whale-watching (WW) operations. This study revealed that large aggregations of BWs consistently overlapped with busy shipping lanes located between Dondra Head and Galle within important foraging and breeding regions on the south coast. Throughout 2015 (except June and July), 729 BWs were sighted over 177 sighting days. The sighting frequency was higher during the northeast monsoon and the first intermonsoon and lower throughout the second intermonsoon (n = 9) and latter part of the southwest monsoon. The highest frequencies of BW encounters per day occurred in April (n = 15) and December (n = 20), while the mean annual group size per sighting was 3.07 ± 0.24. From the January-to-April season, 13 mother–calf combinations and 1 pregnant cow were sighted off the southern coastline of Mirissa, suggesting the calving season peaks between the months of March and April in Sri Lanka. As this important habitat overlapped with the busiest shipping lanes, fishing and commercial whale-watching activities, the authorities have to take action toward the conservation of this ecosystem and whales as well as their safe navigation.